IMVELO (a place for skills development). Construction Centre : Mamelodi : professionals in construction industry in partnership with local community in job creation, upliftment and sustainable environment - Bakker, Karel Anthonie (University of Pretoria, 2013)
Dissertation (MArch(Prof))--University of Pretoria, 2008.